Pattern of Pediatric Oncology Cases in the Western Region of Nepal - Yadav, Pramod Kumar (Asian Pac J Cancer Prev, 2017)
Childhood cancers form a rare and heterogeneous group which fortunately have a higher cure rate than adult cancers. A few non-profit organizations in Nepal have extended support to help patients suffering from cancer, but their main focus has been on adults. The objective of this study was to establish the pattern of childhood cancers in the Western region of Nepal. We reviewed cases receiving external radiotherapy with both palliative and curative intent between 28th September 2010 and 30th September 2015 at the Department of Radiotherapy and Oncology, Manipal Teaching Hospital affiliated with Manipal College of Medical Sciences, Pokhara, Nepal. Of the total of 1217 cases, 2.71% involved children. The gender distribution showed a male preponderance (M:F= 1.35:1). The patients’ mean age was 11.4 years (range 2 - 14 years). Considering the caste, Brahmins and Gurungs constituted 33.0% and 21.2%, respectively, of children with cancer.